(untitled) (Research in Agriculture Livestock and Fisheries, 2018)
Heed Bangladesh has been implementing the LIFT project titled “Accelerating natural breeding of cuchia and creating employment opportunities of poor People through household based cuchia farming” from June to mid-September 2017 in Kamolgonj upazila under Maulvibazar district. The project goal is to reduce poverty and increasing productivity and create self-employment through cuchia rearing by applying modern technology to the poor and marginal people. The initiative will implement mainly with a view to contribute in improving livelihood condition of the small holder cuchia farmers or culturists or rearers who are living in poverty due to natural disaster and climate vulnerability through increasing income. The income of targeted cuchia culturists or members will be increased through increasing productivity, improving quality and market access. Under this initiative, initially a total of 200 members will included. The project focus on building the capacity of members, local service providers, input suppliers and buyers in order to provide embedded or commercial services to the producers and enterprises that will create a competitive market. It will also engage the private and public sector to build the technical capacity of groups and link with high value market to gain a better price for their products. Res. Agric., Livest. Fish.5(2): 279-291, August 2018